Presuming patient autonomy in the face of therapeutic misconception. - McConville, Pat (Bioethics, 2017)
Therapeutic misconception involves the failure of subjects either to understand or to incorporate into their own expectations the distinctions in nature and purpose of personally responsive therapeutic care, and the generic relationship between subject and investigator which is constrained by research protocols. Researchers cannot disregard this phenomenon if they are to ensure that subjects engage in research on the basis of genuine informed consent. However, our presumption of patient autonomy must be sustained unless we have compelling evidence of serious misunderstanding. This article argues that the mere expression of aspects of therapeutic misconception should not necessarily displace the presumption of subject autonomy or undermine ethical inclusion in research for at least three reasons. First, some interpretations of the empirical data do not suggest misunderstanding. Second, assessment of misestimation and optimism are delicate and value-laden, and turn quickly from questions of autonomy to questions of judgment. Third, incomplete understanding may yet be sufficient to allow a subject to engage in a substantially autonomous decision-making process. Our point is not to dismiss the possibility of genuine therapeutic misconception, but to question its frequency and fatality to the consent process.